MECHANISMS AND CONDITIONS OF MAGMA FORMATION IN MANTLE PLUMES - Ryabchikov I.D. (My University, 2003)
Pressures characterizing the formation conditions of near-solidus magmas in plume environments (picrites and meymechites of the Siberian trap province) were estimated on the basis of their TiO2/Na2O ratios and projections onto the phase triangles of the CaO-(Mg, Fe)O-Al2O 3-SiO2 system compared with experimental data. These values were used to calculate the temperature of plume material through a comparison with the pyrolite solidus. The presence of volatile components requires only minor corrections. The estimated temperatures of plume material during the initial stages of magma formation are considerably higher than the temperatures of the upper portion of the asthenosphere, which is consistent with the thermal nature of mantle plumes. The appearance of magmas with high contents of volatile components at the bases of magma generating plumes is explained by the extraction of incompatible components, including volatiles, by near-solidus melts. There is no compelling evidence for the additional input of volatile components, for example by deep fluid flows from the Earth's core. Thus, the concept of "wet spots" has no support.